Preparation and evaluation of liposome with ropivacaine ion-pairing in local pain management. (3rd June 2022) - Ke, Peng; Qin, Yaxin; Shao, Yeting; Han, Min; Jin, Zihao; Zhou, Yi; Zhong, Haiqing; Lu, Yiying; Wu, Xiaodan; Zeng, Kai
Abstract: Local analgesia is one of the most desirable methods for postoperative pain control, while the existing local anesthetics have a short duration of analgesic effect. Nano-drug carriers have been widely used in various fields and provide an excellent strategy for traditional drugs. Although the existing liposomes for local anesthetics have certain advantages, their instability and complexity of the preparation process still cannot be ignored. Here, we developed novel ropivacaine hydrochloride liposomes with improved stability and sustained release performance by combining ropivacaine hydrochloride with sodium oleate in liposomes via hydrophobic ion-pairing (HIP). The liposomes are easy to prepare, inexpensive, and suitable for mass production. The infrared (IR), particle size, and Zeta potential measurements adequately characterized the complex, which showed a diameter of 81.09 nm and a zeta potential of −83.3 mV. Animal behavioral experiments, including the hot plate test and von Frey fiber test, demonstrated that the liposome system had a prolonged analgesic effect of 2 h versus conventional liposome preparations, consistent with the results of in vitro release experiments. In addition, in vitro cytotoxicity evaluations in RAW264.7 cells and in vivo evaluations revealed the biocompatibility and safety of the ropivacaine-sodium oleate ion-paired liposome (Rop-Ole-Lipo) system as a suitable local anesthetic for local pain management. Our findings provide a new idea for the preparation of local anesthetics.